Decolorization and removal of toxicity of textile azo dyes using fungal biomass pelletized - Almeida, E. J.R. [UNESP] (2018)
Abstract: Industrialization and other human impacts have placed increasing pressure on aquatic environments, with the generation of large quantities of toxic aqueous effluents containing different substances, such as synthetic dyes and other organic pollutants. It is estimated that between 10 and 15% of all dyes used in textile processes and other industries are discharged into wastewater, causing extensive aquatic pollution. Biological methods have been employed for the removal of color and toxicity from effluents containing azo dyes. Therefore, biosorption tests were performed with the dyes Acid Blue 161 e Procion Red MX-5B in simple and binary solutions, whereas biodegradation treatment was performed with the dyes only in binary solution. For biosorption, the dyes were removed by the fungi Aspergillus niger, Aspergillus terreus and Rhizopus oligosporus. The fungal biomass demonstrated good adsorption capacity to these compounds. The elimination of the toxicity of the solution after biosorption demonstrated the effectiveness of the treatment. Intense molecular changes after biodegradation treatment with the A. terreus fungus were demonstrated by the FTIR analysis. However, toxicity tests with Lactuca sativa seeds and Artemia salina nauplii indicated the presence of highly toxic metabolites in the reaction medium at the end of the treatment. Based on the findings, biosorption is more suitable for this type of treatment, since it was also capable of removing the molecules from the medium, with the advantage of impeding the formation of highly toxic by-products. Graphical abstract: [Figure not available: see fulltext.]